Research on the Application of SOP in Multi-Station Integrated System - Huo, Qunhai; Wang, Wenyong; Yang, Yanhong; Ma, Ming; Yin, Jingyuan; Wei, Tongzhen (Frontiers in Energy Research, 2021)
The current large-scale access to distributed power and the rapid growth of electric vehicles are seriously affecting the reliability of distribution networks. The new multi-station fusion technology based on the flexible interconnection of the distribution network can effectively solve this problem. In this study, we design a multi-purpose station and a multi-function device using a soft normally open point (SOP). A new multi-station integration topology and a coordinated control strategy are developed using an active power signal (APS) and an energy management system (EMS). The coordinated control strategy involves sending out the corresponding operation mode command after the EMS receives the superior instruction or the APS of the local system and coordinating the operation mode of the SOP, energy storage DC/DC converter, and photovoltaic DC/DC converter, thereby ensuring stable and efficient operation of the multi-station fusion system. Finally, two typical cases are simulated to verify the feasibility and effectiveness of the proposed topology and control strategy.